De beheerste vakbeweging : Het NVV tussen loonpolitiek en loonstrijd 1959-1973 - van Doorn, Kees; Dubbeld, Gerrit; Rosielle, Pieter (Amsterdam: Van Gennep, 1976)
"Kees van Doorn; Gerrit Dubbeld; Pieter Rosielle... et al."